2017
DOI: 10.1148/radiol.2016151985
|View full text |Cite
|
Sign up to set email alerts
|

Yield of CT Pulmonary Angiography in the Emergency Department When Providers Override Evidence-based Clinical Decision Support

Abstract: Purpose:To determine the frequency of, and yield after, provider overrides of evidence-based clinical decision support (CDS) for ordering computed tomographic (CT) pulmonary angiography in the emergency department (ED). Materials andMethods:This HIPAA-compliant, institutional review board-approved study was performed at a tertiary care, academic medical center ED with approximately 60 000 annual visits and included all patients who were suspected of having pulmonary embolism (PE) and who underwent CT pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 37 publications
9
32
2
1
Order By: Relevance
“…Others showed a diagnostic yield of 4.2% among emergency department patients with an unlikely clinical probability. 13 Strikingly, we showed that even those at the highest risk of radiation-induced cancer, young women including pregnant women, had a low diagnostic yield.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Others showed a diagnostic yield of 4.2% among emergency department patients with an unlikely clinical probability. 13 Strikingly, we showed that even those at the highest risk of radiation-induced cancer, young women including pregnant women, had a low diagnostic yield.…”
Section: Discussionmentioning
confidence: 80%
“…The diagnostic yield of CT pulmonary angiograms is low in patients with a low or unlikely clinical probability of pulmonary embolism. 12,13 Most of our patients, however, did not have an objective assessment of clinical probability. Others showed a diagnostic yield of 4.2% among emergency department patients with an unlikely clinical probability.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, clinical decision support tools, built to estimate the pretest probability of PE and discourage the CTPA use in low-risk patients, have been shown to improve the CTPA yield. These tools reduce testing by 25%, without any missed PEs [ 9 , 18 , 19 ]. However, these studies are limited by the time required for manual chart reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Some institutions provide clinical decision support (CDS) at the time of CTPA order by integrating PE risk scoring tools into the electronic health record (EHR); although reductions in overtesting after implementation have been reported, these tools commonly require duplicative, manual data entry to calculate a patient's score . This is time‐consuming and frustrating to providers, leading to decreased use or abandonment of the tool …”
Section: Components and Point Values For The Wells And Revised Genevamentioning
confidence: 99%